Physical and chemical characteristics of tanned chicken feet skin from freshly slaughtered and dead on arrival chickens - Amalia, Dian Nur; Laili Rachmawati; Udkhiyati, Mustafidah; Rosiati, Nur Mutia; Adetya, Nais Pinta; Anggriyani, Emiliana (Jurnal Ilmu Peternakan Terapan, 2026)
Dead on arrival (DOA) animals, particularly poultry, refer to animals that die during the pre-slaughter phase and are generally considered waste, despite their potential as raw materials for leather production. However, scientific information regarding the quality of leather produced from DOA chicken feet skin remains limited. Therefore, this study aimed to evaluate the feasibility of utilizing DOA chicken feet skin by comparing its physical and chemical properties with those of fresh chicken feet skin after tanning. Chicken feet skin from both sources was processed through beamhouse operations, tanning, post-tanning, and finishing stages before quality evaluation. Physical properties analyzed included thickness, softness, shrinkage temperature, elasticity, tensile strength, tear strength, and seam strength, while chemical properties included pH, moisture content, and oil/fat content. Differences between treatments were analyzed using an independent samples t-test for parameters with sufficient replicates. The results showed that thickness, softness, and shrinkage temperature were not significantly different (P>0.05). Fresh and DOA leather showed comparable seam strength values of 602.52 N/cm and 600.23 N/cm, respectively. Chemical properties were also similar, with pH of 4, moisture contents of 15.16% and 13.82%, and oil/fat contents of 14.94% and 14.05%. Overall, DOA chicken feet skin showed comparable characteristics and potential for leather production.